SISTEM PAKAR DIAGNOSA PENYAKIT BUAH NAGA MENGGUNAKAN BACKWARD DAN FORWARD CHAINING - Muhammad Salafuddin; Umi Rosyidah (CCIT Journal, 2017)
Farmersknowledge about dragon fruit disease is still low. Many farmers still rely on the knowledge of an expert to be able to diagnose a disease, so it takes a long and costly. This expert system can be used as information and guidelines for disease that appears on dragon fruit plants and to fill them. Pests on dragon fruit include mealybugs, aphids, ants, grasshoppers, mites and snails. While the disease in dragon fruit include: rust red algae, patches of orange tendrils, white vine, vine blight and anthracnose.The method used is backward chaining and forward chaining, the system is implemented into a web that can be operated by the public, especially dragon fruit farmer. This expert system is an application that uses facts and reasoning techniques that are used by an expert. The use of this expert system can provide information and guidance to users in the form of possible types of diseases that attack the dragon fruit plants based on symptoms entered by the user. This system can provide assistance in the form of services to farmers or farmers plant dragon fruit dragon fruit to diagnose disease in a timely fashion